2013
DOI: 10.1186/1471-2164-14-227
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes related to agarwood formation: transcriptome analysis of healthy and wounded tissues of Aquilaria sinensis

Abstract: BackgroundAgarwood is an expensive resinous heartwood derived from Aquilaria plants that is widely used in traditional medicines, incense and perfume. Only wounded trees can produce agarwood, and the huge demand for the agarwood products has led all Aquilaria spp. being endangered and listed in the Appendix II of the CITES (http://www.cites.org). The major components of agarwood are sesquiterpenes and phenylethyl chromones. Owing to a lack of genomic information, the molecular basis of wound-induced sesquiterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
124
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(151 citation statements)
references
References 66 publications
(86 reference statements)
10
124
0
Order By: Relevance
“…Tyloses are typically induced to form in the embolized vessels by wounding, pathogen attack, and preceding the heartwood formation (Biggs, 1987;Schmitt and Liese, 1993;Taylor et al, 2002;Sun et al, 2006Sun et al, , 2008Pérez-Donoso et al, 2007;Collins et al, 2009), which are the physiological processes in which jasmonates have been implicated (Wasternack and Hause, 2013;Huang et al, 2013;Xu et al, 2013), but no direct involvement of jasmonates in tyloses formation has yet been demonstrated. This study provides the evidence that jasmonates are capable of inducing tyloses and their accompanying gels in plants.…”
Section: Roles Of Jasmonates and Ethylene In Induction Of Tylosesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tyloses are typically induced to form in the embolized vessels by wounding, pathogen attack, and preceding the heartwood formation (Biggs, 1987;Schmitt and Liese, 1993;Taylor et al, 2002;Sun et al, 2006Sun et al, , 2008Pérez-Donoso et al, 2007;Collins et al, 2009), which are the physiological processes in which jasmonates have been implicated (Wasternack and Hause, 2013;Huang et al, 2013;Xu et al, 2013), but no direct involvement of jasmonates in tyloses formation has yet been demonstrated. This study provides the evidence that jasmonates are capable of inducing tyloses and their accompanying gels in plants.…”
Section: Roles Of Jasmonates and Ethylene In Induction Of Tylosesmentioning
confidence: 99%
“…ET concentration was also observed to increase in the transition zone where the heartwood is being formed (Taylor et al, 2002) and during infections (Pérez-Donoso et al, 2007;McElrone et al, 2010); that is, under circumstances in which tyloses are induced. Recent transcriptomics studies of heartwood formation indicated up-regulation of ET and other stress signaling pathways during this process (Huang et al, 2013;Xu et al, 2013). Moreover, the formation of agarwood, which is the commercially valuable heartwood of Aquilaria sinensis, was intensified by applying methyl jasmonate (MeJA) to the cut stems (Xu et al, 2013), implying the involvement of jasmonates in heartwood induction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…White bars represent samples collected from wounded area (S1) while black bars represent samples collected 5 cm below the wounded area (S2) and ethylene, which play known functions in the cross-talk events among organelles and cells under physiological and stress conditions (Zhao et al 2005;Vasconsuelo and Boland 2007;Hou et al 2013). Agarwood formation at the early phase indeed involves wound signalling transduction process through the activation of several transcription factors, such as MYB4, MYC, WRKY4, EIN3, ERF and bZip, which are commonly involved in stress responses (Xu et al 2003). Agarwood sesquiterpene is a typical inducible secondary metabolite; mechanical wounding and chemical treatment are known to induce sesquiterpene substance production.…”
Section: Discussionmentioning
confidence: 99%
“…In Aquilaria, guaiene synthesis has been shown to follow the general terpene synthesis pathway established in higher plants, i.e. the cytosolic mevalonic acid (MVA) pathway (Xu et al 2003). From the building precursor isoprenoid, subsequent enzymatic reactions take place, converting the precursor into several intermediates.…”
Section: Introductionmentioning
confidence: 99%